Interest rates and output in the long-run - Yunus Aksoy; Miguel A. León-Ledesma (European Central Bank (ECB), 2005)
In this paper we argue that both statistics and economic theory-based evidence largely indicate the absence of long run relationships between the real output and the most relevant monetary indicator for the U.K. and the U.S, short term interest rates. These findings are not only a full sample result, but also valid in most of the sub-samples throughout the second half of the 20th century and are robust to the inclusion of possible omitted real variables.
Keywords: E3; E4; E5; 330; bounds tests; cointegration; information value; long term relationship; Informationswert; Zins; Großbritannien; USA; Korrelation